التصور الأجرائي لتقنية القياس الكلفوي للموارد لتحسين فاعلية نظم تكاليف الوحدات الأقتصادية العراقية المطبقة للنظام المحاسبي الموحد في ظل متغيرات بيئة الأعمال المعاصرة - ثائر صبري محمود كاظم الغبانً; فائزة إبراهيم محمود كاظم الغبانً (Journal of Madenat Alelem University College, 2018)
The increasing challenges faced by business organizations in modern industrial environment at present as a result of strong competition pressure and handle multiple clients needs and decision makers at all levels of management as well as the need for appropriate and accurate information and timely criticism of cost management portal leading to there source consumption accounting approach early this century that combines cost assumptions approach on the activity basis cost and the german approach which avoid the most cost mistakes the former cost approaches, and is characterized by its ability to integrate with the methods and practices of modern management accounting in a way that supportsthe different management acts and tasks. research aimed to identifying the impact of integration between enterprise resources planning system and the resource consumption accounting, and it’s reflections on the cost management. This Research aimed to demonstrate the possibility of Resource Consumption accounting approach as one of the alternatives to develop cost systems and in response to changes in modern environment for helping in rationalize and manage resources for Firms, where it has been proposed a framework for Resource Consumption accounting approach can be applicable in Firms, This study has been build on four hypotheses, This study found many of the results: As a result of the development in the Business Firms and the importance of this Business both in terms of humanitarian or economic. The Business Firms have to maintain the element of competition in order to provide product at appropriate prices to enhance the ability to manage resources. The cost accounting systems is one of the main pillars to ensuring the stability of the financial system because of its role to provide decision-makers with financial and non-financial information to enable them to make strategic decisions. The success of the Business Firms is measured largely with achieve profits through the rational use of resources and try to take advantage of the available capacity and reduce costs for the provision of product, and does not come only through the production of accurate scientific means to determine the resources that non values added and work to be avoided in the case of whether these flexible resources or attempt to use the performance of other product if these resources were committed as possible, and this can be achieved through the resource consumption accounting approach. The resource consumption accounting approach Contributes in the solving of the problems facing both the traditional cost accounting systems and activity based costing system in the rationalization of resource management through proper management of resources and try to use the idle capacity and determine the costs ofthe product provided by Product Business Firms accurately and providing useful information to help in the process control, as well as provide information to assist in decision-making and thus achieve a competitive advantage for Product Business.